DEVELOPMENT OF HURDLES MEDIA LEARNING - Supriyanto Balango; Ruslan Ruslan (Universitas Negeri Gorontalo, 2020)
Learning facilities are often a problem in the learning process for athletic sports. The purpose of this study was to produce a product to develop a hurdling learning tool. The subjects of the small scale trial were class IV which assessed 28 students, and the subjects of the large scale trial were class V who were assessed 32 who were in SDN 70 Kota Tengah Kota Gorontalo. The method in this research is related to determining potentials and problems, design data, design validation, revised design, product testing, product testing, usage trials, product revisions, product testing. The results of this development research are in the form of a tool made from a rubber band with adjustable height support poles then poured out and packed into a book.